Salivary MMP-9 Levels in Chronic Periodontitis Patients with Type-II Diabetes Mellitus - Romaisa Arshad; Waleed A. Ismail; Batool Zara; Rabia Naseer; Sadia Minhas; Moeez Ansari; Fatema Akhter; Saria A. Khokhar; Abdullah Ali Alqahtani; Huda Abutayyem; Haytham Jamil Alswairki; Mohammad Khursheed Alam (Molecules, 2022)
Chronic periodontitis and diabetes mellitus share a two-way relationship, the common factor being the inflammatory-mediated pathway, and various cytokines are released during this inflammatory cascade, one of which being matrix metalloproteinase-9. The aim of this study was to identify whether the levels of matrix metalloproteinase-9 are increased due to type-II diabetes mellitus in chronic periodontitis patients. It was an observational, analytical, case-control study. Thirty subjects were recruited in the test group, who were suffering from type-II diabetes mellitus and chronic periodontitis, and 30 subjects in the control group, who were subjects with chronic periodontitis but systemically healthy. Periodontal parameters, including the plaque score, gingival bleeding index, probing pocket depth and clinical attachment level of the subjects, were measured, saliva samples of all of the subjects were collected and salivary matrix metalloproteinase-9 levels were analyzed by an enzyme-linked immunosorbent assay (ELISA) technique. The statistical analysis was performed using SPSS 24. Overall, the matrix metalloproteinase-9 levels of the diabetic patients with chronic periodontitis were increased almost twofold (156.95 ± 29.80 ng/mL) compared to the levels in the controls (74.96 ± 6.32 ng/mL) (p < 0.001). Similarly, the periodontal parameters were far worse in diabetics with chronic periodontitis compared to the controls. The average gingivitis score for the test subjects was 78.45 ± 8.93%), compared to 29.32 ± 12.96% in the controls (p < 0.001). The mean probing pocket depth for the test group was 5.39 ± 0.60 mm, and, for the control group, it was 4.35 ± 0.31 mm (p < 0.001). For the test subjects, the average clinical attachment level was 5.86 ± 0.58 mm, and it was 4.66 ± 0.32 mm for the controls (p < 0.001). It was ascertained that there is a two-fold increase in the levels of salivary matrix metalloproteinase-9 in the test group compared to the control group. In addition, the level of periodontal apparatus destruction was greater in the test group. This proved that type-II diabetes mellitus influences the levels of matrix metalloproteinase-9 in humans and elevates them, causing further periodontal destruction.